(3Odjd eDdaGJ GdMOjK GdTQja GdeWHhYI GdbOjeI hGdMOjKIs - (3YWjI, eMjj GdOjfs; (3Mafj, UdGM GdOjfs; (3jhSa, eMeO NjQ QeVGf,s 1956- ((3HjQhJ (B:s (3OGQ Hf MRe,s, 1995)
(3GdcJGH YHGQI Yf QUO eYdheGJ HHdjhLQGajI Yf cJH GdMOjK GdTQja ef eUGOQ eNJdaI hYdi aJQGJ eJbWYI, agh jTed GdcJH GdeWHhYI hGdQSGFd GdLGeYjI abW Ohf GdcJH GdeOQSjI hGdLGeYjI GdebQQI Ydi GdWdGH(B.s
Keywords: (3GdMOjKs -- (3HHdjhLQGajGJs